FINITE-APPROXIMATE CONTROLLABILITY OF FRACTIONAL EVOLUTION EQUATIONS: VARIATIONAL APPROACH - Mahmudov, Nazim, I (Walter De Gruyter Gmbh, 2018)
In this work we extend a variational method to study the approximate controllability and finite dimensional exact controllability (finite-approximate controllability) for the fractional semilinear evolution equations with nonlocal conditions in Hilbert spaces. Assuming the approximate controllability of the corresponding linear equation we obtain sufficient conditions for the finite-approximate controllability of the fractional semilinear evolution equation under natural conditions. The obtained results are generalization and continuation of the recent results on this issue. Applications to heat equations are treated.
Keywords: fractional calculus; approximate controllability; finite-approximate controllability; fractional ordinary and partial differential equations